PENGGUNAAN METODE DEBAT (STUDENT DEBATE CLUB) UNTUK MENINGKATKAN KETERAMPILAN ARGUMENTASI SISWA DALAM PEMBELAJARAN SEJARAH (Penelitian Tindakan Kelas di Kelas XI IPS 1 SMA Negeri 9 Bandung) - Moh. Firdaus Al Giffari, - (2020)
This thesis is a research result entitled "The Application of the Debate Method (Student Debate Club) to Improve Students Argumentation Skills in Learning History (Class Action Research at XI IPS 1 SMA Negeri 9 Bandung)". This research was motivated by the findings of researchers at XI IPS 1 Class in SMA Negeri 9 Bandung which showed that students were still lacking in argumentation skills. This can be seen from the majority of students who just quiet when the teacher given the opportunity to ask questions or make some arguments, and when asked by the teacher these students didn't understand. Therefore, the researchers conducted a class action research conducted in three cycles. Each of the cycles is performed one action using the Class Action Research (CAR) model of Kemmis and McTaggart designs, the process of which consists of planning, implementing, observing, and reflecting. Indicators of the argumentation skills used are courage in argumentation, sound regulation when arguing, attitude in argumentation, and the argumentation skills. Sub-indicators of the argumentation skills are used confidence in expressing arguments, not questioning the correctness of the arguments, sounding clear, fluent when speaking, appreciating the arguments of others, criticizing the arguments of others wisely, delivering arguments logically and analytically, and conveying arguments based on argumentation. The acquisition of argumentation skills scores has increased in each cycle. Increasing the percentage of each cycle shows the effectiveness of the application of the debate method (Student Debate Club) to improve students' argumentation skills in learning history.